KONSEP QIWĀMAH (KEPEMIMPINAN SUAMI) DALAM RUMAH TANGGA: KAJIAN TEMATIK TERHADAP HADIS BUKHĀRI NO. 2558 - Inatul Mufida (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study aims to examine the concept of Qiwāmah (husband's leadership) in the household based on the hadith narrated by Imām al-Bukhārī No. 2558. The hadith explains the responsibilities and roles of men as leaders in their families. This study uses a thematic study method on hadiths related to Qiwāmah, with a primary focus on analysing the text, context, and scholars' understanding of the hadith. The approach used is a qualitative approach with descriptive analysis through a review of hadith commentary books, interpretations, and classical and contemporary literature. The results of this study show that the concept of Qiwāmah in Bukhari Hadith No. 2558 is not a form of male superiority over women, but rather an affirmation of the moral, spiritual, and material responsibilities of husbands guided by the values of justice, compassion, and deliberation in making household decisions. In the context of modern life, the meaning of Qiwāmah needs to be understood proportionally as leadership oriented towards cooperation and balance of roles between husband and wife, not domination. Thus, Bukhārī Hadith No. 2558 provides a strong normative basis for the formation of a sakinah family through fair, responsible, and compassionate leadership.